2017
DOI: 10.1038/s41598-017-12560-8
|View full text |Cite
|
Sign up to set email alerts
|

A tunable electron beam source using trapping of electrons in a density down-ramp in laser wakefield acceleration

Abstract: One challenge in the development of laser wakefield accelerators is to demonstrate sufficient control and reproducibility of the parameters of the generated bunches of accelerated electrons. Here we report on a numerical study, where we demonstrate that trapping using density down-ramps allows for tuning of several electron bunch parameters by varying the properties of the density down-ramp. We show that the electron bunch length is determined by the difference in density before and after the ramp. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 27 publications
1
32
2
Order By: Relevance
“…Interestingly, the data show that the emittance decreases almost exponentially as the down ramp length increases. We note that other numerical studies have shown contradictory results; i.e., the emittance of the injected beam either decreases [36] or increases [37] for a longer down ramp. This discrepancy as well as the exponential decrease of the emittance we observed are worth being checked in an experiment.…”
Section: Sensitivity Of Ramp Variations On Emittance and Currentmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, the data show that the emittance decreases almost exponentially as the down ramp length increases. We note that other numerical studies have shown contradictory results; i.e., the emittance of the injected beam either decreases [36] or increases [37] for a longer down ramp. This discrepancy as well as the exponential decrease of the emittance we observed are worth being checked in an experiment.…”
Section: Sensitivity Of Ramp Variations On Emittance and Currentmentioning
confidence: 55%
“…The data show that, even for the most abrupt down ramp (L ¼ 5 c=ω p ), the slice emittance of the beam is about 0.1 μm. We note that simulations of laser-driven down ramp injection show that the generation of beams with an emittance as low as ∼0.2 μm is achievable [36,37].…”
Section: Sensitivity Of Ramp Variations On Emittance and Currentmentioning
confidence: 84%
“…A semi-analytical model to predict the injected beam length and the injection threshold in arbitrary downramps was then derived [22]. A study on the influence of the transition downramp steepness on the beam quality has then been presented in [23]. The studies in [20][21][22][23] employ different laser parameters, thus together they constitute a coherent but somewhat fragmented study of the density transition injection technique.…”
Section: Introductionmentioning
confidence: 99%
“…An example can be seen with the LPI where the down-ramp injection technique mentioned above is applied. Typically, sharper down ramps lead to more captured charges but induce a larger emittance, an effect that is accentuated by a larger density jump before and after the ramp [57]. By tuning the sharpness of the ramp and the density jump, a compromise can be obtained so that the desired emittance and charge can be reached [32].…”
Section: B High Beam Quality and High Beam Charge Issuesmentioning
confidence: 99%